ANALYZING EXPORT TRADE AND ITS IMPACT ON EMPLOYMENT IN CHINA'S BORDER AREAS - Turner, Alex (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The relationship between trade and employment has emerged as a critical focus in contemporary international trade research, particularly in the context of the deepening integration of the global economy and the utilization of globalized labor resources. However, long-term studies on the impact of export trade on employment have predominantly centered on China's coastal provinces, leaving western regions, especially border areas, relatively unexplored. This research gap is significant because the influence of exports on employment is intricately shaped by geographical location, industrial composition, and openness to international markets. For instance, in 2010, despite increased export trade in eastern, central, and western regions of China, the eastern region experienced a substantial gain of nearly 80 million jobs since 2000, while the central and western regions saw a more modest increase of about 30 million. Furthermore, certain border provinces witnessed the paradoxical scenario of rising export trade volumes coupled with a decline in employment, prompting intriguing questions.